FAST POSITIONING PERFORMANCE IN BALL SCREW MECHANISM WITH DISTURBANCE OBSERVER (Jurnal Teknologi (Sciences & Engineering), 2016)
Ball screw mechanisms are widely applied in different industries due to their capability in achieving precise positioning performance as well as its long travel range for positioning, travelling and contouring actions. However, this mechanism exhibits nonlinearities in micro movement. In this paper, a disturbance observer and PD controller (PDDO) is proposed in ball screw mechanism to achieve fast and precise positioning performance. A macrodynamic mathematical model of the mechanism is derived. PDDO controller is designed to achieve fast positioning in micro travel range. The robustness of the controller against mass is examined. The experimental results demonstrated that the PDDO controller achieves better performance in fast tracking (3 Hz) with working range at 100 Î¼m, 1 mm and 3 mm as compared to the PID controller. Besides that, the PDDO controller also demonstrated its robustness in the presence of mass changes.